2017
DOI: 10.1002/met.1606
|View full text |Cite
|
Sign up to set email alerts
|

Observed changes in temperature extremes for the Beijing–Tianjin–Hebei region of China

Abstract: As one of the most significant threats facing the world, climate change has already been manifested everywhere in the form of frequent extreme climate events (e.g. heat waves, floods, droughts and wildfires) and has caused serious impacts on all aspects of the living environment. Due to the regional variability of global climate change, understanding the ongoing climatic changes at a local scale is very important for decision makers and resource managers to develop appropriate mitigation and adaptation strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…In the aforementioned studies, extreme precipitation indices as recommended by the Expert Team on Climate Change Detection and Indices (ETCCDI) and parametric and non-parametric statistic tests (for example, Mann-Kendall test, Sen's slope, and Pettit tests) were applied to detect the trends in precipitation extremes in different temporal scales. Additionally, this approach has been broadly used for studies on trend analysis of climatology in recent years (Wang et al 2016;Zhang et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the aforementioned studies, extreme precipitation indices as recommended by the Expert Team on Climate Change Detection and Indices (ETCCDI) and parametric and non-parametric statistic tests (for example, Mann-Kendall test, Sen's slope, and Pettit tests) were applied to detect the trends in precipitation extremes in different temporal scales. Additionally, this approach has been broadly used for studies on trend analysis of climatology in recent years (Wang et al 2016;Zhang et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al have investigated the temporal and spatial features of precipitation in the BTHR using observational data for 1965-2014 [19]. Zhang et al have observed changes in extreme temperature events at eight meteorological stations in the BTHR [20]. Clearly, considering the rapid development occurring in the BTHR, a comprehensive examination of temporal trends in extreme precipitation and temperature events and their spatial heterogeneities using up-to-date and long-term observations is necessary to formulate adaptive strategies for extreme climate events.…”
Section: Introductionmentioning
confidence: 99%
“…(Figure 3a), with increasing temperatures (Zhang et al 2017), but is not reflected over the longer timeframe presented here .…”
Section: Spi Analysis and Temporal Variability Of Droughts 1724-2019mentioning
confidence: 70%
“…After the Western Zhou Dynasty (approximately ~1046-771 BC), the inscription of bronze Dynasty (317-420 AD) paper became much widely used for records, which is the main source for many of the ancient books (Needham and Tsuen-Hsuin 1985;Zhang 2004b).…”
Section: Documentary Datamentioning
confidence: 99%